2012
DOI: 10.1007/s00228-012-1423-2
|View full text |Cite
|
Sign up to set email alerts
|

Orphan drugs, orphan diseases. The first decade of orphan drug legislation in the EU

Abstract: Although there may have been some small improvements over time in the methods for developing OMPs, in our opinion, the number of patients studied, the use of placebo as control, the type of outcome measure and the follow-up have often been inadequate. The present system should be changed to find better ways of fostering the development of effective and sustainable treatments for patients with orphan diseases. Public funds supporting independent clinical research on OMPs could bridge the gap between designation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 8 publications
4
87
0
10
Order By: Relevance
“…11 A more recent systematic review of orphan drug legislation in Europe also advocated for more stringent approval criteria for evaluating the clinical and costeffectiveness of orphan drugs. 12 Another systematic review of orphan drugs used in cancers showed that they have varying levels in quality of evidence and dearth of information on economic value. 13 While the first two reviews did not evaluate the quality of the evidence, the third review focused only on drugs marketed in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…11 A more recent systematic review of orphan drug legislation in Europe also advocated for more stringent approval criteria for evaluating the clinical and costeffectiveness of orphan drugs. 12 Another systematic review of orphan drugs used in cancers showed that they have varying levels in quality of evidence and dearth of information on economic value. 13 While the first two reviews did not evaluate the quality of the evidence, the third review focused only on drugs marketed in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of this definition is that between 5,000 and 8,000 different rare diseases affect or will affect around a total of 29 million patients in the whole EU. 1 Traditionally, patients suffering from rare diseases have been a marginalized patient group because of limited scientific knowledge about the respective diseases, the low number of patients, lack of medical expertise among health care professionals, and restricted awareness about rare diseases in the public, and thus only a few medicines have been marketed for the treatment of rare diseases. 1 In order to promote and enhance the development of medicines for treatment of rare diseases, a central European licensing system for the approval of orphan drugs was established in 2000 in the EU.…”
Section: Introductionmentioning
confidence: 99%
“…Так, в Евросоюзе этот вопрос находится в юрисдикции Комитета по орфан-ным медицинским продуктам Европейского медицинского агентства (European Medicines Agency, EMA) [16]. В стра-нах EC признание продукта орфанным дает фармацевти-ческим компаниям различные преференции, такие как 10-летний статус эксклюзивного производителя, содей-ствие в составлении протокола клинического исследова-ния, снижение взносов для проведения исследований под эгидой EMA и предоставление грантов на клинические исследования [17]. С момента принятия соответствующих законов в 2000 г. в Евросоюзе было зарегистрировано 106 орфанных лекарственных средств [18].…”
Section: результаты и обсуждениеunclassified
“…В США и странах ЕС используют разные подходы к предоставлению исключительного (монопольного) пра-ва продажи -ключевого, с точки зрения фармацев-тических компаний, стимула для разработки орфанных препаратов. В Евросоюзе, где соответствующий зако-нодательный акт был принят в 2000 г., это означает, что в течение 10 лет зарегистрированный продукт может производить исключительно держатель регистрационно-го удостоверения, хотя для одного и того же заболевания на рынке могут иметься несколько разных наимено-ваний лекарственных средств [17,22]. В США данная привилегия касается только действующего вещества препарата.…”
Section: результаты и обсуждениеunclassified